Exploring Innovative Work Behavior among Vocational Educators: A Qualitative Study in Private Vocational Schools in Indonesia - Reza Dwi Ramadhan; Umi Anugerah Izzati; Olievia Prabandini Mulyana (MASI Mandiri Edukasi, 2026)
As the demands of the modern workforce evolve, the capacity of vocational educators to innovate becomes increasingly critical. However, research on innovative work behavior (IWB) has predominantly focused on public or general education settings, leaving a gap in understanding how IWB manifests in private vocational schools, which often face more acute resource constraints and market pressures. This study examines teachers’ IWB at a private vocational high school in East Surabaya, Indonesia. Employing a qualitative descriptive design, the study investigates how educators generate, promote, and implement innovative practices within the school context. Data were collected through semi-structured in-depth interviews with 12 participants, including school administrators and teachers across various vocational disciplines, and analyzed using Miles and Huberman’s interactive model. Findings reveal that while educators demonstrate robust IWB use, their innovation is specifically triggered by